A mathematical team to solve problems (Edma 0-6: Educación Matemática en la Infancia, 2021)
The relation between mathematics and movies or TV series goes beyond the purely anecdotal. The books where various authors have compiled mathematical references and educational suggestions, as well as the available training courses for teachers, are a proof for this. Animated cartoons produced for children and distributed as entertainment media also include mathematics: counting, arithmetic, measures, chance, geometry, etc., often immersed in common situations. Or not so common, as it is not strange that cartoons arguments are about adventures with spaceships, fairies and elves, or animals that speak. However, these situations are close to the children and they will allow to propose educational sequences around this resource. On the other hand, animated cartoons with mathematical references play a fundamental role in the progressive construction of children's personal meanings and beliefs about mathematics. We start this section with a very special team, Team Umizoomi, who are experts in problem solving.
Keywords: Early Childhood Education; Mathematics; Animated cartoons; Audio-visual fiction